Impact of Time to Neonatal Transport on Outcomes of Transient Tachypnea of the Newborn - Hirata, Katsuya; Nozaki, Masatoshi; Mochizuki, Narutaka; Hirano, Shinya; Wada, Kazuko (American Journal of Perinatology, 2019)
Objective To assess effects of neonatal transport on transient tachypnea of the newborn (TTN) in outborn term neonates.Study Design This retrospective cohort study included 66 term neonates diagnosed with TTN and transported to the Osaka Women's and Children's Hospital neonatal intensive care unit between January 2003 and March 2018. A multivariate logistic regression analysis identified perinatal and neonatal transport factors associated with adverse short-term outcomes defined as mechanical ventilation >48 hours, continuous positive airway pressure >72 hours, pulmonary hemorrhage, and requirement for inhaled nitric oxide, thoracentesis, or surfactant replacement therapy.Results A lower gestational age (GA) (37.7 [37.2, 38.3] vs. 39.6 [37.8, 40.3] weeks, p = 0.002), longer time to neonatal transport (10.0 [4.3, 25.5] vs. 5.5 [2.7, 9.7] hours, p = 0.01), and higher respiratory rates during transport (70 [60, 85] vs. 60 [55, 78.8] breaths/min, p = 0.04) were significantly associated with adverse short-term outcomes. After adjusting for GA, sex, cesarean section, and time to neonatal transport, GA (odds ratio [OR], 0.37; 95% confidence interval [CI], 0.24–0.87) and time to neonatal transport (OR, 1.07; 95% CI, 1.01–1.13) were significantly associated with adverse outcomes.Conclusion Short-term adverse prognosis of TTN is strongly associated with a lower GA and longer time between birth and neonatal transport.
Keywords: neonatal; neonatal transport; outborn term neonate; transient tachypnea of the newborns